THE IMPACT OF COVID-19 ON ELDERLY DAY CARE A CASE STUDY IN BANGKOK, THAILAND - Nakarait Na Pattalung; Maniga Thongkong (The Indonesian Journal of Public Health, 2026)
Introduction: The global epidemic of COVID-19 caused enormous disruptions in communities and institutions around the world. 6.71% of people in Thailand became infected. Aims: This qualitative study aimed to investigate the various impacts of the COVID-19 epidemic on elderly day care services in Bangkok, Thailand. Methods: Data were gathered by in-depth interviews and focus group. A total of 40 participants were involved, comprising elderly individuals, their family members, caregivers, and day care center managers. Results: The results showed that the pandemic had an impact on elderly day care services in four major domains: (1) prevention of infectious diseases; (2) physical and mental health care, showing a decrease in regular health monitoring and an increase in psychological distress among the elderly; (3) social isolation, showing a notable decrease in social engagement and a rise in isolation; and (4) caregivers, caregivers should have knowledge in physical health, mental health, and infection prevention. Conclusion: In conclusion, in order to improve the resilience of senior care systems in the face of upcoming public health emergencies, our findings point to the necessity of adaptive care models that include mental health assistance, creative forms of social interaction (such as digital technologies), and modern caregiver.